2022
DOI: 10.3390/antibiotics11060786
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Two MDR Isolates of Salmonella enterica Serovar Infantis from a Spanish Hospital Bearing the blaCTX-M-65 Gene with or without fosA3 in pESI-like Plasmids

Abstract: Salmonella enterica serovar Infantis (S. Infantis) is a broiler-associated pathogen which ranks in the fourth position as a cause of human salmonellosis in the European Union. Here, we report a comparative genomic analysis of two clinical S. Infantis isolates recovered in Spain from children who just returned from Peru. The isolates were selected on the basis of resistance to cefotaxime, one of the antibiotics of choice for treatment of S. enterica infections. Antimicrobial susceptibility testing demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Furthermore, recently pESI-like megaplasmids were revealed in Russia [ 18 , 19 ]. These plasmids are conjugative with up to 300 kb length and harbor AMR genes including ESBL genes, as well as genes conferring resistance to tetracyclines, sulphonamides, and aminoglycosides [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recently pESI-like megaplasmids were revealed in Russia [ 18 , 19 ]. These plasmids are conjugative with up to 300 kb length and harbor AMR genes including ESBL genes, as well as genes conferring resistance to tetracyclines, sulphonamides, and aminoglycosides [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infantis isolated from broilers and humans in Italy ( Franco et al, 2015 ), in E. coli from cattle in the Netherlands ( Dantas Palmeira and Ferreira, 2020 ) and more recently from beef and pork samples collected at retail in Portugal ( Leão et al, 2021 ) and in S . Infantis from human cases in Spain ( Vázquez et al, 2022 ). To the best of the authors’ knowledge, this is the first reported case of a bla CTX-M-65 isolated from the environment in Ireland.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance (AR) plays an important role in the increased incidence of different bacterial infections. Indeed, the high level of resistance and multi-drug resistance (MDR) recorded in S. Infantis in multiple countries (i.e., Italy, Hungary, Germany, Russia, United States) can be considered another reason for the epidemiological success of this serovar [ 13 , 14 ]. The extended AR exhibited by Salmonella species and other pathogenic bacteria is due to the use and misuse of antibiotics in humans and animals (both in livestock and aquaculture species); these latter, moreover, may spread antibiotic-resistant bacteria (ARB) via their faces and contaminate the terrestrial and marine environment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%